2021
DOI: 10.3390/diagnostics11091626
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Treatment Modalities, and Potential Contributing and Prognostic Factors in Patients with Bone Metastases from Gynecological Cancers: A Systematic Review

Abstract: The purpose of this study is to review the clinical characteristics, treatment modalities, and potential contributing and prognostic factors of bone metastases from gynecological cancers (GCs). A systematic literature search on PubMed, Scopus, Web of Science Core Collection and Cochrane Central Register of Controlled Trials databases was conducted. Thirty-one studies, all retrospective, were included in this review, for a total of 2880 patients with GC bone metastases. Primary tumors leading to bone metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Despite the low reported incidence of bone metastasis from EC, autopsy series have shown a significantly higher incidence of about 35% [ 25 , 26 ], emphasizing the need of accurate clinical surveillance and screening after primary cancer. Furthermore, it was reported that the vertebral column represents the most common site of EC bone metastasis [ 7 , 8 ]. Despite these data, to date, only one case-series on six patients reported the clinicopathological characteristics, surgical outcomes, survival, and complications following surgery for vertebral bone metastases from different gynecological cancers, i.e., cervical cancer, EC, and leiomyosarcoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low reported incidence of bone metastasis from EC, autopsy series have shown a significantly higher incidence of about 35% [ 25 , 26 ], emphasizing the need of accurate clinical surveillance and screening after primary cancer. Furthermore, it was reported that the vertebral column represents the most common site of EC bone metastasis [ 7 , 8 ]. Despite these data, to date, only one case-series on six patients reported the clinicopathological characteristics, surgical outcomes, survival, and complications following surgery for vertebral bone metastases from different gynecological cancers, i.e., cervical cancer, EC, and leiomyosarcoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…EC bone metastases are uncommon, and the rate is estimated to be <1% [ 6 ]. The most common site for EC bone metastasis is the vertebral column, followed by the pelvis and long bones [ 7 , 8 ]. The causes of this ”preferentially spread” have not yet been fully understood, but it has been hypothesized that the cellular and molecular characteristics of cancer cells and the tissues to which they metastasize are critical and affect the pattern of metastatic spread.…”
Section: Introductionmentioning
confidence: 99%